Diagnosis and treatment progress of pulmonary thromboembolism - LI Jiandong, GUO Shanfeng, ZHOU Tao, MIAO Qinghai, SHAO Zefeng (Zhongguo linchuang yanjiu)
Pulmonary thromboembolism (PTE) is one of the most common types of pulmonary embolism. In the past, due to the backward diagnostic technology and the lack of understanding of clinicians about PTE, and the lack of specificity of PTE symptoms, it often led to missed diagnosis and misdiagnosis. Sometimes, even if PTE is diagnosed in time, due to the lack of treatment means and experience of doctors, patients often cannot get timely and effective treatment, resulting in poor prognosis and high fatality rate. In recent years, with the continuous standardization of PTE diagnosis and treatment protocols, the fatality rate has shown an obvious downward trend. Therefore, this article summarizes the recent progress in the diagnosis and treatment of PTE at home and abroad.